Morphological spectrum of neovaginitis in autologous sigmoid transplant patients. Issue 7 (21st December 2015) - van der Sluis, Wouter B; Neefjes‐Borst, Eskelina A; Bouman, Mark‐Bram; Meijerink, Wilhelmus J H J; De Boer, Nanne K H; Mullender, Margriet G; van Bodegraven, Adriaan A
Abstract : Aims: Autologous intestinal grafts are used to (re)create a vagina in selected patients. The risk of diversion colitis is mentioned as a disadvantage, although its prevalence remains unclear. This study aimed to assess the histopathological characteristics of the sigmoid‐derived neovaginal epithelial lining after diverting surgery and correlate these with clinical findings. Methods and results: Biopsy specimens were obtained from the epithelial lining of the sigmoid‐derived neovagina and remaining rectosigmoid as regular follow‐up from 26 patients with a median age of 22 years (range 19–52) and median postoperative follow‐up of 13 months (range 6–52). Medical history, neovaginal symptoms and sexual activity were documented. An experienced gastrointestinal histopathologist assessed the specimens using a descriptive item‐score, comprising signs of chronic and active inflammation. Inflammatory changes were observed in 21 (80.7%) neovaginal and one (3.8%) rectosigmoid specimens. The neovaginal appearance was characterized by an increase of lymphoid aggregates and lymphoplasmacellular infiltrate. Other common features were the presence of polymorphonuclear neutrophils and Paneth cell metaplasia. Neovaginal discharge was correlated with the presence of inflammatory changes ( P = 0.008, Spearman's rho = 0.506). Discussion: Acute and chronic inflammation of the sigmoid‐derived neovagina was commonly observed and consistent with a proposed diagnosis of diversion neovaginitis. Neovaginal discharge correlates with this histopathological entity.